The Impact of The Region Transport Infrastructure and Services on The Social and Economic Performance of Russian Regions - Anna Yu. KOSOBUTSKAYA1; Irina A. DYADYUN2; Marina N. PISKOVATSKAYA2 (Communications of International Proceedings, 2020)
The article is devoted to the analysis of correlation between transport infrastructure indicators and social and economic performance in a region. Correlation analysis of the given indicators for 57 subjects of the Russian Federation located in the European part of the country was carried out. As a result, a high correlation between the state of transport infrastructure and services of road transport as its part, and the indicators characterizing social and economic development of regions was identified. The study uses logical and econometric analysis to perform calculations and verify the results. The revealed correlation also confirms the efficiency of regions’ transport infrastructure investments in terms of complex social and economic effect. The correlation suggests the transport infrastructure indicators maximally connected with the development of the region for influencing, helps to forecast the impact of the transport infrastructure investments on the development of the economy, growth of the living standards indicators in the region.
Keywords: Region Economy; Transport Infrastructure; Correlation; Service Infrastructure of Road Transport.